Comparison of Outcomes of Enoxaparin Bridge Therapy in HeartMate II versus HeartWare HVAD Recipients. (September 2021) - Patel, Mitulkumar; Ahuja, Tania; Arnouk, Serena; Gidea, Claudia; Reyentovich, Alex; Smith, Deane E.; Moazami, Nader; Papadopoulos, John; Lewis, Tyler C.
Background: There is a lack of robust data evaluating outcomes of enoxaparin "bridge" therapy in left ventricular assist device (LVAD) patients. Methods: We performed a retrospective study of HeartMate II (HM II) and HeartWare HVAD recipients that received therapeutic enoxaparin as "bridge" therapy to describe bleeding and thrombotic events and compare outcomes between devices. The primary endpoint was the incidence of bleeding within 30 days of "bridge" episode. Major bleeding was defined by INTERMACS criteria. Results: We evaluated 257 "bridge" episodes in 54 patients, 35 with a HM II device and 19 with an HVAD device that underwent 176 and 81 bridging episodes, respectively. The median INR prior to "bridge" was lower in the HM II group compared to the HVAD group (1.5 vs 1.7, P < .01), however, there was no difference in the median duration of "bridge" therapy (7 vs 7 days, P = .42). There were a total of 30 (12%) bleeding episodes, with the majority in the HM II group vs HVAD (26 [15%] vs 4 [5%], P = .02). We observed 3 (1%) thromboembolic events in 2 (4%) patients with an HVAD device. On multivariate analysis, the presence of a HM II device was associated with a 4-fold increased risk of bleeding. Conclusion: We found the use of enoxaparin "bridge" therapy to be associated with a higher incidence of bleeding in patients with a HM II device compared with an HVAD device. Assessment of device- and patient-specific factors should be evaluated to minimize bleeding events.